Comparison of ventilation-perfusion single-photon emission computed tomography (V/Q SPECT) versus dual-energy CT perfusion and angiography (DECT) after 6 months of pulmonary embolism (PE) treatment. Issue 9 (September 2015) - Meysman, M.; Everaert, H.; Buls, N.; Nieboer, K.; de Mey, J.
Highlights: Incomplete resolution of pulmonary emboli occurs frequently. Residual V/Q-SPECT defects correspond in the majority of cases with defects seen on DECT. Some (11.1%) defects on V/Q-SPECT are not present on comparable DECT images. Abstract: Background: The natural evolution of treated symptomatic pulmonary embolism shows often incomplete resolution of pulmonary thrombi. The prevalence of perfusion defects depend on the image modality used. This study directly compares V/Q SPECT with DECT. Methods: A single-center prospective observational cohort study of patients with intermediate risk PE, reassessed at the end of treatment with V/Q SPECT. Abnormal V/Q SPECT images were compared with DECT. Results: We compared DECT en V/Q SPECT in 28 consecutive patients with persistent V/Q mismatch on V/Q SPECT, 13 men and 15 woman, mean age 60 (+ 17), range 23–82 year. One patient was excluded from the final analysis due to inferior quality DECT. In 18/27 (66.7%) the results were concordant between CTPA (persistent embolus visible), DECT (segmentary defects on iodine map) and V/Q SPECT (segmentary ventilation–perfusion mismatch). In 3/18 (11.1% of the total group) the partialy matched V/Q SPECT defect could be explained on DECT lung images by lung infarction. In 6/27 (22.1%) only hypoperfusion was seen on DECT iodine map. In 3/27 (11.1%) results were discordant between V/Q SPECT and DECT images. Conclusion: Six months after diagnosis of first or recurrent PE, residual pulmonary perfusion-defects encountered on V/Q-SPECT corresponds in the majority of patients with chronic thromboembolic disease seen on DECT. In 22.1% of patients V/Q SPECT mismatch only corresponds with hypoperfusion on iodine map DECT scan. Some (11.1%) of the chronic thromboembolic lesions seen on V/Q SPECT can not be explained by DECT results.